2008
DOI: 10.1016/j.drugalcdep.2007.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Traveling young injection drug users at high risk for acquisition and transmission of viral infections

Abstract: Background: Young injection drug users (IDU) are highly mobile. It is not known how mobility affects their risk of acquiring and transmitting viral infections. Methods:We conducted a cross-sectional study of young (under age 30) IDU in San Francisco (2004)(2005)(2006). Participants completed a semi-structured interview and testing for hepatitis B virus (HBV), hepatitis C virus (HCV) and HIV infection. We examined whether travel was independently associated with drug, alcohol, sexual risk behaviors, and infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
31
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 26 publications
(25 reference statements)
1
31
1
Order By: Relevance
“…Morissette, 2008; Thibault, Bara, Nefau, & Duplessy-Garson, 2011), and backloading or frontloading (using a N/S to prepare and divide drugs between other N/S) (Hahn, Page-Shafer, Ford, Paciorek, & Lum, 2008;Jose et al, 1993;Maher, Li, Jalaludin, Chant, & Kaldor, 2007;Platt et al, 2009). Many studies have investigated the association between sharing N/S and HCV but, despite this, only one study has reviewed/meta-analysed this association .…”
Section: And 2 and 3 Andmentioning
confidence: 99%
“…Morissette, 2008; Thibault, Bara, Nefau, & Duplessy-Garson, 2011), and backloading or frontloading (using a N/S to prepare and divide drugs between other N/S) (Hahn, Page-Shafer, Ford, Paciorek, & Lum, 2008;Jose et al, 1993;Maher, Li, Jalaludin, Chant, & Kaldor, 2007;Platt et al, 2009). Many studies have investigated the association between sharing N/S and HCV but, despite this, only one study has reviewed/meta-analysed this association .…”
Section: And 2 and 3 Andmentioning
confidence: 99%
“…In two independent studies, greater than 37% of young IDUs engaged in heavy or problem drinking (Campbell et al, 2006;Hahn et al, 2008), a troubling association given that alcohol increases the risk of initial HCV exposure progressing to chronic disease (Piasecki et al, 2004;Thomas et al, 2000). This is especially pertinent among IDUs, who already face elevated risk of chronic HCV infection.…”
Section: T He Continued Spread Of Hepatitis C Virusmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] Older age and longer injecting duration could account for the higher upper bounds of these estimates; however, two U.S. studies 8,9 reported finding 33 and 36 % of IDUs under 25 years old were HCV infected and several non-U.S. studies found a much higher prevalence even among IDUs in this age group. 10 In 2007, 48 % of individuals with incident HCV in the U.S. reported injection drug use, which continues to be the leading risk factor for infection.…”
Section: Introductionmentioning
confidence: 99%